Is hepatojugular reflux a good predictor of heart failure with preserved ejection fraction? - Baldivia,Guilherme Cristianini (2019)
SUMMARY Hypertension may occur with left ventricular (LV) diastolic dysfunction, and the consequence may be symptoms and signs of heart failure (HF). Hepatojugular reflux (HJR), described as a sign of regurgitation of the tricuspid valve, may reflect structural and functional changes of the LV in the hypertensive patient. The signal may be present in the presence of HF. Case: male, 49 years old with uncontrolled blood pressure. Physical examination showed jugular turgescence, HJR, and elevated blood pressure. Complementary exams showed signs of atrial and left ventricular overload in the electrocardiogram and, the echocardiogram showed left atrium volume increase, concentric LV hypertrophy and signs of grade I diastolic dysfunction. DISCUSSIO: The HJR present correlates with pulmonary artery pressure and probably reflect the increase in central blood volume.